2007
DOI: 10.1055/s-2007-965420
|View full text |Cite
|
Sign up to set email alerts
|

Facts and Fiction about Sulfur Metabolism in Relation to Plant‐Pathogen Interactions

Abstract: Sulfur deficiency developed into a widespread nutrient disorder in the 1980s because of the drastic decrease of SO(2) emissions in western Europe after Clean Air Acts came into force. It was observed that not only the yield and quality of agricultural crops were negatively affected by sulfur deficiency but also their health status. Since the mid 1990s the physiological background of this latter phenomenon in the sulfur metabolism has been studied by different researchers. From 2001 until 2006, field trials wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 85 publications
(81 reference statements)
1
61
0
Order By: Relevance
“…For instance, sulfur supply has been implicated in resistance to pathogens (Bloem et al, 2007). Although the underlying causes of this phenomenon remain to be identified, tissue contents of glutathione or precursors could be one of the factors linking sulfur nutrition to the responses of plants to fungal and viral infection (Bloem et al, 2007;Höller et al, 2010). A threshold level of glutathione has been shown to be necessary for production of the phytoalexin camalexin and also to determine pathogen resistance (Parisy et al, 2007).…”
Section: Ascorbate and Glutathione As Ros-independent Signalsmentioning
confidence: 99%
“…For instance, sulfur supply has been implicated in resistance to pathogens (Bloem et al, 2007). Although the underlying causes of this phenomenon remain to be identified, tissue contents of glutathione or precursors could be one of the factors linking sulfur nutrition to the responses of plants to fungal and viral infection (Bloem et al, 2007;Höller et al, 2010). A threshold level of glutathione has been shown to be necessary for production of the phytoalexin camalexin and also to determine pathogen resistance (Parisy et al, 2007).…”
Section: Ascorbate and Glutathione As Ros-independent Signalsmentioning
confidence: 99%
“…The nutritional status with essential plant nutrients and their balance contribute signifi cantly to the physiological predisposition of a plant against fungal infections. Experimentation in the fi eld of sulphur (S) nutrition and plant disease provided added indications that the S status of a plant is particularly critical during the initial phase of pathogenesis, and if several stress factors coincide, while its signifi cance declines with spread of the disease in the host (Salac et al, 2006;Bloem et al, 2007;Haneklaus et al, 2007a). In this context it should be noted that evaluating the nutritional status of a plant correctly is not as easy as commonly assumed.…”
Section: Nutrient-induced Resistance Against Diseases 1111mentioning
confidence: 99%
“…A distinct increase in cysteine in host tissue and emissions of H 2 S was found in the initial phase of pathogenesis (Kruse et al, 2005;Bloem et al, 2007). It might be speculated that enrichment with S 0 affects the pathogen most in the initial phase of development, after adhesion of conidia and germ tube formation, but before penetration by appressoria, since Kassemeyer (2003) found the highest effi ciency of foliar-applied S 0 against powdery mildew of grapes at this stage of germling development.…”
Section: Fungitoxicity Of S Metabolites 1123mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding with T. cacao reminds the redox-active properties of glutathione (GSH/ GSSH) which fulfils protective functions when plants are exposed to biotic or abiotic stress (Rausch et al 2007). Moreover, Bloem et al (2004Bloem et al ( , 2007 reported that the infection of Brassica napus L. with Pyrenopeziza brassicae increased cysteine and glutathione contents, as well as the activity of l-cysteine desulfhydrase. It could therefore be assumed that the tolerance of T. cacao hybrids to P. megakarya depends on the availability and mobilisation ability of sulphate, cysteine, and glutathione which are used for the synthesis of sulphurous antibiotic molecules (metabolites, peptides, …) against the biotic stress due to P. megakarya.…”
mentioning
confidence: 99%